The Sociology of Food and Nutrition - Barham, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This class explores individual food choices and larger social forces. Topics include: world hunger, food and the environment; food choices and culture, class and personal identity; the effects of social stigmas, advertising trends, and government regulation on body image; new social movements for sustainable food systems.